2016
DOI: 10.1002/marc.201600203
|View full text |Cite
|
Sign up to set email alerts
|

Precision Chain‐Walking Polymerization of trans‐4‐Octene Catalyzed by α‐Diimine Nickel(II) Catalysts Bearing ortho‐sec‐Phenethyl Groups

Abstract: α-Diimine nickel complexes bearing bulky ortho-sec-phenethyl groups (bis{[N,N'-(4-methyl-2,6-di-sec-phenethylphenyl)imino]-1,2-dimethylethane}dibromonickel (1), bis{[N,N'-(4,6-dimethyl-2-sec-phenethylphenyl)imino]-1,2-dimethylethane}dibromonickel (2), bis{[N,N'-(4-methyl-2-sec-phenethylphenyl)imino]-1,2-dimethylethane}dibromonickel (3)) and {bis[N,N'-(2,4,6-trimethylphenyl)imino]-1,2-dimethylethane}dibromidonickel (4) are used as a precatalyst for the polymerization of trans-4-octene upon activation with modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…In the process of exploring various Brookhart catalysts, various olefinic monomers have been polymerized and copolymerized. 27,31,[125][126][127] The applicable monomers have also been rapidly growing to include linear 128,129 and branched 130,131 α-olefins, cycloalkyl substituted α-olefins, 132-136 cycloolefins, 137 dienes, 138 trienes, 139,140 internal olefins, [141][142][143][144] norbonene type monomers, [101][102][103][104] and different polar comonomers. 3,27,28 It should be noted that the continuous interest in Brookhart-type catalysts largely originates from their capabilities in copolymerizations of olefins with polar functionalized comonomers.…”
Section: Copolymerizations Of Olefins With Polar Monomersmentioning
confidence: 99%
“…In the process of exploring various Brookhart catalysts, various olefinic monomers have been polymerized and copolymerized. 27,31,[125][126][127] The applicable monomers have also been rapidly growing to include linear 128,129 and branched 130,131 α-olefins, cycloalkyl substituted α-olefins, 132-136 cycloolefins, 137 dienes, 138 trienes, 139,140 internal olefins, [141][142][143][144] norbonene type monomers, [101][102][103][104] and different polar comonomers. 3,27,28 It should be noted that the continuous interest in Brookhart-type catalysts largely originates from their capabilities in copolymerizations of olefins with polar functionalized comonomers.…”
Section: Copolymerizations Of Olefins With Polar Monomersmentioning
confidence: 99%
“…In the field of polyolefin research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], many studies have reported on the homopolymerization of ethylene [ 21 , 22 , 23 , 24 ], different higher 1-alkene [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], and linear internal alkenes [ 32 , 33 , 34 ] using Brookhart-type α-diimine nickel and palladium catalysts [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ] because of the chain-walking process [ 42 , 43 , 44 , 45 ]. The interest in highly branched polyolefins such as dendrimer and hyper branched polymers has increased obviously in recent years owing to these unique physical properties, chemical properties, and their potential applications as adhesives, lubricants, and paints [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nickel catalysis has been shown to be more successful at polymerizing internal alkenes due to their higher activity, although initial work from Brookhart indicated a strong preference for trans isomer; no polymerization of cis ‐2‐butene was reported . In 2017 Shiono and co‐workers reported successful homopolymerization of a range of 2‐alkenes from a nickel diimine catalyst . Nickel catalysts have shown further potential in the polymerization of internal olefins, although block copolymers with 1‐alkenes have never been reported.…”
Section: Introductionmentioning
confidence: 99%